Asset Insulators. (22nd May 2020) - Chodorow-Reich, Gabriel; Ghent, Andra; Haddad, Valentin
Abstract: We construct a new data set tracking the daily value of life insurers' assets at the security level. Outside of the 2008–2009 crisis, a ${\$}$ 1 drop in the market value of assets reduces an insurer's market equity by ${\$}$ 0.10. During the ?nancial crisis, this pass-through rises to ${\$}$ 1. We explain this pattern by viewing insurance companies as asset insulators, institutions with stable, long-term liabilities that can ride out transitory dislocations in market prices. Illustrating the macroeconomic importance of insulation, insurers' market equity declined by ${\$}$ 50 billion less than the duration-adjusted value of their securities during the crisis.